An analysis of the boundary conditions model influence on the ground temperature profile determination - Jaszczur, Marek; Polepszyc, Inga; Dudek, Michał (Computer Assisted Methods in Engineering and Science, 2015)
In this work, the influence of boundary conditions model (environmental model) on the ground temperature profile is analyzed. A numerical model for transport phenomena in the area above the top ground surface and below in the ground is presented. The results of simulation- ground temperature profile and mean seasonal temperature which estimate the energy potential of the ground are presented. In addition, the results of implementation of five different environmental models for the area above the top ground surface are presented. It is found that none of the models is able to reproduce the temperature variation similar to the reference (most complex) model accuracy. On the other hand, it is found that with a slight error a similar result for low ground depth can be obtained using the simplest Model 1.